(untitled) (Revista Brasileira de Contabilidade e Gestão, 2023)
Objective(s): This study aims to analyze what engagement marketing actions the Fapi Náutica brand can adopt to add value to its brand equity. Method(s): A quantitative approach was used with a descriptive method and a case study research technique. A questionnaire was given to all active company customers in 2022. Results: Our main results indicate that most clients have knowledge about the performance of the brand in the market and claim that it transmits security and confidence in its processes, attributing greater importance to these factors than the practiced price, which users considered higher than that of the competition. Results also suggest that the company shows logistic loss-making, with insufficient distribution outside the state of Rio Grande do Sul and available sales formats. Contributions: We conclude that the theme of this study is important not only for its theoretical reflections on brand equity and engagement marketing but also for the professional environment due to its updated content and increasing relevance for companies precisely because they produce satisfactory results and efficient solutions. Thus, the studied company can, based on our results, better understand its performance and develop new strategies to improve its function.